Halal Industry Research Trends: A Bibliometric Study - Judijanto, Loso (West Science Islamic Studies, 2025)
The halal industry has emerged as a rapidly expanding global sector, extending beyond food into areas such as cosmetics, pharmaceuticals, logistics, and finance. This study aims to map the scholarly landscape of halal industry research through a bibliometric analysis of Scopus-indexed publications from 2000 to 2024. Using VOSviewer software, the study visualizes keyword co-occurrence networks, temporal trends, and density distributions to identify dominant themes, emerging topics, and research gaps. Results reveal that early research was dominated by themes such as halal food, certification, and consumer trust, while recent studies have shifted focus toward blockchain technology, sustainability, and halal supply chain management. The analysis also uncovers a growing interdisciplinary convergence, with contributions from marketing, supply chain, technology, and regulatory studies. Despite significant advancements, underexplored areas such as halal cosmetics, fintech, and green development present opportunities for future inquiry. This study contributes to a deeper understanding of how halal research has evolved and offers insights for scholars, practitioners, and policymakers to align research agendas with industry transformation.